Keberhasilan PBB dalam Penanggulangn Masalh Tentara anak di Liberia Melalui Program DDRR - Abdul Pikqi P; Anik Yuniarti (Jurnal Paradigma, 2013)
During the civil war in Liberia, many children are involved in wars as a child soldiers. They have served in various field of the war. Regarding to this situation, United Nations ran the DDRR (Disarmament, Demobilization, Rehabilitation and Reintegration) program which succeeded in reducing the number and involvement of child soldiers in Liberia. It was also integrated the children into the communities where they originated. The program was successfully implemented by several supporting factors namely: leadership, momentum, participation of all parties, salient solution and the government policy on the national agenda of Liberia.